The Christian education health check: A survey for understanding church school climate - McLure, Felicity; Aldridge, Jill (2022)
Understanding students’ perceptions of Christian education is essential for schools seeking to make changes that enhance opportunities for students to understand and engage with Christian faith. This study introduces and describes the validation of an accessible survey that probes students’ perceptions of the Christian culture of their school and the degree to which the school culture has influenced their willingness to engage with and adopt a faith stance. Schools can use the survey to identify areas for change related to the school climate, teaching and social-emotional learning, in conversation with teachers and students.